Schedule of Classes, Winterim 2010 - University of Wisconsin-Milwaukee. Department of Enrollment Services (My University, 2010)
PDF version of the UW-Milwaukee Schedule of Courses for the Winter 2010 term. Includes registration policies and lists of available classes during this term.